2014
DOI: 10.4238/2014.february.19.7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of zinc transporter 3 and carbonic anhydrases 2 and 14 mRNA expression in the retina of rats affected by low dietary zinc

et al.

Abstract: ABSTRACT. We looked at how zinc transporter 3 ZnT-3) mRNA expression in the rat retina is affected by low dietary zinc. Groups of 12 four-week-old male Sprague Dawley rats were fed on a low-zinc diet for 2, 4 or 6 weeks. Half of each group was then fed with a normal-zinc content diet and the other half was given a low-zinc content diet. The expression of ZnT-3, carbonic anhydrase 2 (CA2) and 14 (CA14) were detected by RT-PCR. After the rats were fed a low-zinc content diet for 2 weeks, their retina CA2 and CA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Since then, an increasing amount of research has shown that diet influences local retinal zinc homeostasis. Zinc supplementation results in a higher amount of intracellular retinal zinc, whilst a zinc‐deficient diet induces retinal gene expressional changes . Light‐induced retinal degeneration and visual cell loss in rats resulted in gene expressional changes (attributed to inflammation, apoptosis, cytokines, the innate immune response, and related receptors) and this type of induced retinal degenerative change was shown to decrease in response to the addition of a zinc oxide, plus rosemary, antioxidant mixture .…”
Section: Suboptimal Dietary Zinc Status and Deficiency: Clinical Manimentioning
confidence: 99%
“…Since then, an increasing amount of research has shown that diet influences local retinal zinc homeostasis. Zinc supplementation results in a higher amount of intracellular retinal zinc, whilst a zinc‐deficient diet induces retinal gene expressional changes . Light‐induced retinal degeneration and visual cell loss in rats resulted in gene expressional changes (attributed to inflammation, apoptosis, cytokines, the innate immune response, and related receptors) and this type of induced retinal degenerative change was shown to decrease in response to the addition of a zinc oxide, plus rosemary, antioxidant mixture .…”
Section: Suboptimal Dietary Zinc Status and Deficiency: Clinical Manimentioning
confidence: 99%